ECO-BRANDING PADA PRODUK KOSMETIK LOKAL INDONESIA - Kurnia Budhy Scorita; Aisyah Pia Asrunputri (JURNAL ADMINISTRASI KANTOR, 2022)
Local Indonesian cosmetic products are currently starting to dominate in their own country, there are many choices of cosmetic / skincare products in Indonesia, only those that carry the concept of eco branding are still small, even though currently young people in Indonesia have a very high interest in environmental concepts, and this used by some cosmetic manufacturers by promoting environmentally friendly cosmetic products. Of course the eco-branding concept applied aims to increase trust and interest in buying products. This is certainly an interesting theme to study. This research method uses a qualitative research approach with descriptive analysis of literature reviews in national journals systematically from eco-branding theory using the Publish or Perish application and VOS Viewer. The results of the study show that eight Indonesian local cosmetics have fulfilled aspects of the eco-branding theory. Keywords: Eco Branding, Cosmetic Products, Environmentally Friendly